PENGARUH (INISIASI MENYUSU DINI) IMD TERHADAP JUMLAH PERDARAHAN KALA IV DI KLINIK PRATAMA TANJUNG KECAMATAN DELI TUA TAHUN 2023 - Hadi, Milvan; Siregar, Ripai; Tamimi, Aisyah (Deli Medical and Health Science Journal, 2023)
One of the MGDS global targets is to reduce MMR and IMR. The maternal mortality rate in Indonesia is still high at 390 per 100,000 live births. Referring to the link between birth management and various countermeasures for the biggest cause of AKI is postpartum hemorrhage. Efforts have been made in problems related to bleeding, even several studies have carried out IMD in treating bleeding problems considering that the presence of IMD can affect the hormone oxytocin which is associated with bleeding. The purpose of this study was to see how IMD influences the amount of bleeding in the fourth stageThis research is a quasi-experimental study using control and experimental groups. The population and sample were all mothers who gave birth as many as 16 respondents using the Purposive Sampling method. The data were analyzed univariately and bivariately using the Mann-Whitney test.The results showed that there was a significant effect between IMD on the amount of bleeding in the fourth stage. The average number of bleeding in the fourth stage of respondents who underwent Early Breastfeeding Initiation was 4.50 with a standard deviation of 12.683. Meanwhile, respondents in the control group averaged the amount of bleeding in the fourth stage was 12.50 with a standard deviation of 19.291. In the statistical test, the value of P = 0.001 <a0.05 was obtained With this study, it was found that there was an effect of IMD on the amount of bleeding in the fourth stage of labor. It is hoped that midwives and doctors will implement IMD in order to reduce morbidity and mortality of mothers and babies.